A new approach to ancient microorganisms: taxonomy, paleoecology, and biostratigraphy of the Lower Cambrian Berkuta and Chulaktau microbiotas of South Kazakhstan. (28th March 2016) - Schopf, J. William; Sergeev, Vladimir N.; Kudryavtsev, Anatoliy B.
Abstract: Peritidal cherts and silicified phosphorites of the Early Cambrian Kyrshabakta (Berkuta Member) and Chulaktau formations of South Kazakhstan contain diverse assemblages of cellularly permineralized microorganisms that like other microbiotas of similar age and setting are dominated by cyanobacteria, both filamentous (oscillatoriacean trichomes and empty sheaths) and coccoidal (chroococcaceans). Although these near-shore assemblages contain sphaeromorph acritarchs, they differ from Neoproterozoic and Early Cambrian microbiotas of more open-marine environments by lacking morphologically complex planktonic eukaryotes such as the acanthomorphic acritarchs that are abundant in the Chulaktau-overlying Shabakta Formation. In general composition, the Berkuta and Chulaktau assemblages are similar both to microfossil assemblages of the pre-trilobite Rovno and Lontova Regional Stages of the East European Platform and to Early Cambrian microbiotas known from chert-phosphorite deposits worldwide. The studies reported here are based on use of optical microscopy combined with techniques recently introduced to paleobiology: confocal laser scanning microscopy, and Raman and fluorescence spectroscopy and imagery. Taken together, these provide information in situ, in three dimensions and at high spatial resolution, about the organismal morphology; cellular anatomy; chemical composition; and mode, fidelity, and environment of preservation of the permineralized microfossils. Data are presented suggesting that the substitution of samarium for calcium in fossil-preserving apatite may provide evidence of its oxic or anoxic paleoenvironment of formation. We interpret the Berkuta and Chulaktau assemblages to be composed of 27 taxa assigned to 17 genera of microscopic prokaryotes and eukaryotes that include one new genus and species, Berkutaphycus elongatus .